Analisis Hambatan Belajar Mata Kuliah Matematika Dasar pada Mahasiwa Jurusan Gizi - Nurasiah, Lilis; Alan Rusyadi (Program Studi Pendidikan Matematika, Universitas Pancasakti Tegal, 2022)
This study aims to analyze: student errors in solving function problems of learning basic mathematics subject. The place of research was carried out at Al-Ihya Kuningan Islamic University, odd semester in 2021.2022 academic year. This research is classified as a qualitative descriptive study that seeks to describe the analysis of student learning obstacles. The research population was all nutrition students at Al-Ihya Kuningan Islamic University who took basic mathematics subject. The research subjects were taken random by 5 people who took basic mathematics courses in the odd semester of the 2021/2022 Academic Year. This research used diagnostic tests, questionnaires and interviews instrument. From the research, it can be concluded: (1) the students ability and motivation to learning basic mathematics is low; (2) students' mistakes in general are because they do not understand the questions and have low pre-concepts; (3) different methods were used for each class meeting to find solutions to overcome these obstacles. The solution was to provide test or questions relevant to what they learned and the mathematical subject, use understandable language then explained the solution